Approach to family screening in arrhythmogenic right ventricular dysplasia/cardiomyopathy. (27th August 2015) - te Riele, Anneline S.J.M.; James, Cynthia A.; Groeneweg, Judith A.; Sawant, Abhishek C.; Kammers, Kai; Murray, Brittney; Tichnell, Crystal; van der Heijden, Jeroen F.; Judge, Daniel P.; Dooijes, Dennis; van Tintelen, J. Peter; Hauer, Richard N.W.; et al.
Abstract : Aims: A combination of variable expression, age-related penetrance, and unpredictable arrhythmic events complicates management of relatives of arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) patients. We aimed to (i) determine predictors of ARVD/C diagnosis and (ii) optimize arrhythmic risk stratification among first-degree relatives of ARVD/C patients. Methods and results: Detailed phenotypic and outcome data of 274 first-degree relatives (46% male; 36.5 ± 18.9 years) of 138 ARVD/C probands were obtained. Ninety-six (35%) relatives were diagnosed with ARVD/C according to 2010 Task Force Criteria (TFC). Siblings had a three-fold-increased risk of ARVD/C diagnosis compared with parents and children (odds ratio 3.11, P < 0.001). Multivariable logistic regression identified symptoms ( P < 0.001), being a sibling ( P < 0.001), the presence of a pathogenic mutation ( P < 0.001), and female sex ( P = 0.010) as predictors of ARVD/C diagnosis. During 6.7 ± 3.8 years of follow-up, 21 (8%) relatives experienced a sustained ventricular arrhythmia (cycle length 271 ± 48 ms). While being a sibling was a predictor of ARVD/C diagnosis, neither relatedness to the proband ( P = 0.185) nor malignant family history ( P = 0.347) was significantly associated with arrhythmic events. Meeting TFC independent of family history criteria had higher prognostic value for arrhythmic events than conventional 2010 TFC, which include family history [area under the receiver operating characteristic curve 0.95 (95% CI 0.93–0.97) vs. 0.85 (95% CI 0.82–0.88), P < 0.001]. Conclusion: One-third of first-degree relatives develop manifest ARVD/C. Siblings have highest risk of disease, even after correcting for age and sex. Fulfilment of TFC independent of family history is superior to conventional TFC for arrhythmic risk stratification of relatives.